The Impact and effect of caffeine on the improvement of muscle strength of students in the college of physical education and sports at Al-Aqsa University - Dr. Nadir Ismaeel Halawa; Dr. Husham Ali Alaqraa (الرياضة المعاصرة)
The study aimed to acknowledge the impact of caffeine on the improvement of muscle strength of students in the college of physical education and sports at Al-Aqsa University, the researchers used the descriptive method, and the sample (21 students) were a first-year physical education and sports students. The most important result was that one hour after the caffeine were taken, there was a significant change in the results of the muscle force tests, as follows: For strength endurance, the stomach test had time (30 seconds), the improvement rate was 11.45%. For pressure testing, the rate of improvement was 11.45%. And the pressure of the inclined recline test, the improvement rate was 13.51%, As for the speed, the broad jump test, the improvement rate reached 7.27%, To test the thrust of the medical ball, the improvement rate was 7.91%, As for the maximum strength component of the dead lift test, the improvement rate was 9.53%, and for the knee bending test, the improvement rate was 7.5%. For chest push ups testing, the improvement rate was 10.64%. Caffeine was used as a nutritional supplement containing caffeine anhydrous in an amount of 200 mg, from 2.5 to 3.5 mg/kg each dose of student's weight. Additionally, many previous references that include caffeine were scanned, which our study matched with some of these ones, using the average dose